"Pretty Tough and Pretty Hard": An Intersectional Analysis of Krump as Seen on So You Think You Can Dance. Issue 4 (2nd October 2021) - Rose, Victoria; Barrick, Simon; Bridel, William
ABSTRACT: Krump, a form of street dance that is often characterized as aggressive and unique in its expression, has received little attention in academic scholarship. Research that has been published has largely focused on the American-made documentary RIZE (2005), with critiques emerging regarding its problematic-racialized representations of krump. No literature to date has focused on krump and its performances of gender. In the present study, the authors explored representations of krump on the popular dance competition television show, So You Think You Can Dance ( SYTYCD) and YouTube comments posted in relation to said performances. Analysis of qualitative materials was influenced by the tenets of intersectionality, with the aim of understanding the interconnectedness of gender and race in popular representations of krump. Emergent and intersecting themes included performing hardness, negotiation of idealized gender performances, the reproduction of traditional notions of whiteness and blackness, and ghettoization.